Modality therapy for Dementia Management: A Systematic Review - Putu Intan Daryaswanti; Ni Made Diah Pusparini Pendet; Komang Agus Jerry Widyanata (Proceeding of International Conference on Science, Health, And Technology, 2019)
Old age has a higher risk for suffering from dementia. Although there is currently no cure for dementia, there are several modality therapies that can be applied to help deal with complaints that arise in dementia. This study aims to identify the effect of modality therapy on cognitive, physiological and psychological changes in dementia patients. A systematic review was conducted, we performed a systematic review on Science direct, PubMed, Ebsco, Web of Science, Cinahl, Research Gate database for relevant articles. Studies were included if the interventions with modality therapy were carried out in Dementia patients, both those treated at home and nursing homes. A total of 17 articles were included and 3 main categories emerged: cognitive, physiological, and psychological. Some therapeutic studio modalities can improve cognitive and physiological. Of these three categories, the category of psychological change is most often found. Psychological changes in depression, delusions and hallucinations (psychosis), agitation, apathy, aggression, sleep disturbance and disinhibition (inappropriate social relations and sections). The provision of modality therapy can help improve psychological problems of patients treated both at home and in nursing homes, and this modality therapy can be recommended in providing implementation and activities tailored to the patient's characteristics and controlling external factors to achieve therapeutic effectiveness.